The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/bmc.1097
|View full text |Cite
|
Sign up to set email alerts
|

Binding and elution strategy for improved performance of arginine affinity chromatography in supercoiled plasmid DNA purification

Abstract: New interesting strategies for plasmid DNA (pDNA) purification were designed, exploiting affinity interactions between amino acids and nucleic acids. The potential application of arginine-based chromatography to purify pDNA has been recently described in our work; however, to achieve higher efficiency and selectivity in arginine affinity chromatography, it is essential to characterize the behaviour of binding/elution of supercoiled (sc) isoforms. In this study, two different strategies based on increased sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
1
11
0
3
Order By: Relevance
“…Arginine-agarose support was recently used to effectively purify pDNA [17] (supercoiled and open circular) [9], and it was suggested that the binding mechanism involves phenomenological interactions like biorecognition between amino acids and pDNA [14], including, electrostatic interactions, hydrophobic interactions, (multiple) hydrogen bond interactions, dipole-dipole forces, cation-p interactions, etc. Since plasmids are negatively charged due to the phosphate groups in the DNA backbone, it is easy to predict a favourable electrostatic interaction between the plasmid phosphate groups and arginine ligands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arginine-agarose support was recently used to effectively purify pDNA [17] (supercoiled and open circular) [9], and it was suggested that the binding mechanism involves phenomenological interactions like biorecognition between amino acids and pDNA [14], including, electrostatic interactions, hydrophobic interactions, (multiple) hydrogen bond interactions, dipole-dipole forces, cation-p interactions, etc. Since plasmids are negatively charged due to the phosphate groups in the DNA backbone, it is easy to predict a favourable electrostatic interaction between the plasmid phosphate groups and arginine ligands.…”
Section: Resultsmentioning
confidence: 99%
“…This amino acid also facilitates elution of bound proteins from various column resins, including Protein-A or dye affinity [35] columns and hydrophobic interaction columns [33]. More recently it was demonstrated that this competition strategy with arginine in elution buffer is capable of the total elution of pDNA indicating that the interaction of pDNA with the matrix was weakened by competition [9,14]. In this work, the elution of the oligonucleotides by addition of an arginine-supplemented buffer was tested.…”
Section: Arginine In Elution Buffermentioning
confidence: 95%
See 1 more Smart Citation
“…7,9 Positively charged amino acids covalently conjugated to chromatography resin have been used to purify plasmid DNA through a combination of ion exchange and affinity chromatography. 9,11 …”
Section: Introductionmentioning
confidence: 99%
“…Within the group of pseudobiospecific ligands, we can find small ligands (e.g., thiophilic, metal chelating), which are quite general and lack selectivity for specific targets (Batalha et al, 2012;Pina et al, 2014), for example imac, amino acid ligands (Sousa et al, 2009(Sousa et al, , 2010(Sousa et al, , 2011 expression in eukaryotic cells systems, and purification mostly relies on resins with protein A, which increases their production cost (Skerra, 2007). Antibodies are less stable in very harsh differences in pH, use of organic solvents, and high salt concentrations can lead to denaturation (W€ orn and Pl€ uckthun, 2001).…”
Section: Pseudobiospecificmentioning
confidence: 99%